ANALYSIS OF ECOTOURISM AND DISASTER MITIGATION DATA AT THE KUALA LANGSA MANGROVE FOREST BY USING THE ANALYTIC HIERARCHY PROCESS - Arif, Salmawaty; Akmalia, Nanda (PATTIMURA UNIVERSITY, 2024)
The problem in the management of a public area is to determine aspects that contribute most as its best practices. This paper explores the contributions of the Kuala Langsa Mangrove Forest located in Langsa City, Aceh Province, for ecotourism and disaster mitigation. This research was intended to analyze the aspects of forest management that has successfully reformed dry coast into an ecotourism site. The Analytic Hierarchy Process (AHP) as a multicriteria decision making method was used to analyze the best indicators data. This method was selected as the suitable method since it utilizes the objectivity of mathematics in comparing some subjective criteria to obtain the best indicators. The implementation of the AHP method consists of three stages: the development of the criteria’s hierarchy table; the development of pairwise matrix related to the intention of giving weights for the criterion’s elements; the logical concistency verification of the matrix. Indicators were written on a five point scale related to a value judgement. The results of the research show that as an ecotourism site, the activities of the mangrove forest are motivated and based on the existing rules which attract people to become interested. The role of the local government has resulted: developed the programs according to the existing mangrove management law that reached 67% among other law related indicators; budget allocation priority by self-generating which get priority of 59% among budget indicators; oriented on the increasing of fishermen, obtained 49% of economical function elements; encouraged the involvement and partnership of the local resources around the mangrove forest which reached 31% among other programs offered and sustainability approach by considering ecological functions aspect. For physical contribution for disaster mitigation, the largest dissipation is given by Rhizophora mucronata due to its height compared to the other types.